2001
DOI: 10.1081/ncn-100105907
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Selenium-Derivatized Nucleosides and Oligonucleotides for X-Ray Crystallography

Abstract: We report here the synthesis of nucleoside and oligonucleotide analogs containing selenium, which serves as an anomalous scattering center to enable MAD phase determination in nucleotide X-ray crystallography. We have developed a phase transfer approach to introduce the selenium functionality in A, C, G, T, and U nucleosides at 5'-positions. In the incorporation of the selenium functionality, the leaving groups (bromide, mesyl, and tosyl) were readily displaced by sodium selenide, sodium diselenide, and sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
62
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

7
2

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 20 publications
0
62
0
Order By: Relevance
“…[12][13][14][15][16][17] The use of selenomethionyl proteins for multiwavelength anomalous-dispersion (MAD) phasing has revolutionized the field of protein X-ray crystallography. [18,19] This derivatization of proteins with Se has also been applied successfully in RNA structure determination through indirect derivatization of RNA that binds to the Se-derivatized protein.…”
mentioning
confidence: 99%
“…[12][13][14][15][16][17] The use of selenomethionyl proteins for multiwavelength anomalous-dispersion (MAD) phasing has revolutionized the field of protein X-ray crystallography. [18,19] This derivatization of proteins with Se has also been applied successfully in RNA structure determination through indirect derivatization of RNA that binds to the Se-derivatized protein.…”
mentioning
confidence: 99%
“…In the case of a novel protein structure, the phase problem is usually solved by the selenomethionine (Se-Met) derivatization and multiwavelength anomalous dispersion (MAD) technique (Hendrickson 1991;Deacon and Ealick 1999). Inspired by the convenient Se-derivatization of proteins, since 1998, Huang's research group has pioneered and developed the selenium derivatization of nucleic acids for X-ray crystallography (Carrasco et al 2001;Caton-Williams and Huang 2008;. We found that the selenium-derivatized RNAs and DNAs are stable and that the selenium derivatizations do not cause significant perturbation Salon et al 2007Salon et al , 2010Sheng et al 2007Sheng et al , 2011Caton-Williams and Huang 2008;Olieric et al 2009;Hassan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the natural system, our laboratory pioneered the atom-specific replacement of nucleotide O with Se ( Fig. 2) in order to obtain new insights into nucleic acid structures, and biological functions and mechanisms [38] [39]. It is exciting to explore chemical, physiological, biochemical, and structural properties of the Se-derivatized DNAs and RNAs, which also leads to a new paradigm for nucleic acids.…”
mentioning
confidence: 99%
“…Chemical synthesis of Se-derivatized nucleic acid is achieved via the solid-phase synthesis strategy by using the phosphoramidite building blocks [38] [39]. Prior to the synthesis of Se-labeled nucleic acids, there are many hurdles to overcome, including protecting and deprotecting group strategies for the Se functionalities, solubilization of the free nucleosides, the compatibility of the Se functionalities on solid-phase synthesis, and the stability of Se-derivatized nucleic acids.…”
mentioning
confidence: 99%